THE RELEVANCE OF THE INFLUENCE AND IMPORTANCE OF ACTIONABLE GAMES IN IMPROVING THE INTELLECTUAL CAPACITY OF YOUNG ATHLETES (American Journal of Pedagogical and Educational Research, 2024)
Sport is a universal tool that helps it feel physically and spiritually great. Sports are especially useful for kids. When engaging in sports, a child develops physical abilities and, moreover, makes new friends, learns to be part of the team, the principles of fair play, appreciates himself and enjoys itself. Experts believe that children need to be personally exemplary in order to instil love for sports. The second most effective factor that allows children to get used to sports is to create conditions for this. As with life in sports, defeat is an integral part of the process. It is important that the sport after training does not make a bad impression on them. It is important to prevent your child from associating sports with negative emotions. Your child needs to make sure the sport does not cause stress, but rather relieves it.